PELATIHAN PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) RAMAH LINGKUNGAN (BAHAN BEKAS) UNTUK MENINGKATKAN KREATIVITAS GURU - Firda, Tuti Firdayani; Novianti, Rahmah; Padillah; Andriani, Dessi; Jaya, Melinda Puspita Sari; Intan, Fatma Rizki; Idayana, Santa (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
Educational Game Tools (APE) can be said to be used as a means or playing device with educational (teaching) value and can develop the abilities of all children. Utilization of APE using eco-friendly materials (used materials) has benefits in supporting the teaching and learning process, namely as a means or equipment for playing that contains educational value, develops the concept of cause and effect, has the potential to stimulate brain growth, and develops all aspects of children's abilities, more over it invites Early Childhood Education teachers to be more creative and innovative in developing APE by utilizing eco-friendly materials (used materials).